Quantification of carbon sequestration in unlogged lowland dipterocarp forest, Semenyih, Malaysia using CO2FIX V3.1 model - Abdullah, Fazlyzan (2012)
Carbon dioxide (CO2) is one of greenhouse gasses (GHG’s) that cause of global warming and climate change. Carbon sequestration through forestry sector is one of mechanisms in removal of CO2 from the atmosphere with the least cost. Therefore, 1 ha plot was established at Sungai Lalang Forest Reserve, Semenyih, Selangor to quantify carbon sequestration in an unlogged forest using inventory methods, allometric equations and modeling. CO2FIX V3.1 Model was used because it suitable for tropical forest, user friendly and required less data. Besides, litter fall study and litter bag experiment was conducted to determine litter fall for estimate carbon flow from plant to soil pool and determine decomposition rate of leaf litter. Results from simulation model CO2FIX showed carbon stocks in 1 ha study plot at Sungai Lalang Forest Reserve were decreased from year 1 of simulation period (522.04 Mg C/ha) to year 100 (229.98 Mg C/ha). Meanwhile, results from calculation using allometric equation for year 2007 to 2008 showed carbon stocks were increased from 564.38 Mg C/ha to 592.25 Mg C/ha and decreased to 501.43 Mg C/ha for year 2009. This study concluded that carbon stock in Sungai Lalang Forest Reserve was in steady state of a mature forest because simulation results of CO2FIX showed after a few years total carbon increase,then it suddenly drops and maintain. This study also found that litter fall and decomposition process play an important role in carbon flow from plant to soil which representing one of the major pathways of nutrient cycling. Results of litter bag experiment showed leaves decomposed from fastest to slowest, in the following order: Diospyros sumatrana Miq > Elateriospermum tapos Blume > Macaranga triloba (Blume) Müll.Arg. All leaf types examined were decomposed significantly different each other depends on litter quality such as Carbon/Nitrogen ratio and Nitrogen. This study also discovered that carbon potential was influenced by species composition, tree density, and growth characteristics of tree. Therefore, strategies for carbon mitigation plan of forestry options can be planned through the knowledge gained from these findings. Species with high carbon stocks values are suggest to be selected for afforestation and reforestation activities to enhance the carbon potential of forest.